Characterization of a Panel of Monoclonal Antibodies to Human Coagulation Factor XI and Detection of Factor XI in Hep G2 Cell Conditioned Medium - Ohkubo, Y; O’Brien, D P; Kanehiro, T; Fukui, H; Tuddenham, E G D (Thrombosis and Haemostasis, 1990)
We have produced a panel of ten monoclonal antibodies specific to coagulation factor XI. Western blot analysis demonstrates that 9 of these antibodies react with the heavy chain of factor XI and one with the light chain. Seven of these antibodies inhibit factor XI and factor XIa activity.We have used immobilised monoclonal antibody for the production of factor XI deficient plasma and to purify factor XI to homogeneity with high yield in a simple two-step procedure. These monoclonal antibodies were used to develop highly sensitive immunoassays capable of detecting less than 0.01 u factor XI antigen ml−1. A strong correlation was found between antigen and activity levels in 11 patients with hereditary deficiency indicating that none was cross-reacting material positive. Cultured Hep G2 cells were found to synthesize small amounts of factor XI antigen and this could also be detected by functional assay and by western blot analysis.